2009
DOI: 10.1111/j.1365-2656.2009.01545.x
|View full text |Cite
|
Sign up to set email alerts
|

Social group size affects Mycobacterium bovis infection in European badgers (Meles meles)

Abstract: Summary 1.In most social animals, the prevalence of directly transmitted pathogens increases in larger groups and at higher population densities. Such patterns are predicted by models of Mycobacterium bovis infection in European badgers ( Meles meles ). 2. We investigated the relationship between badger abundance and M. bovis prevalence, using data on 2696 adult badgers in 10 populations sampled at the start of the Randomized Badger Culling Trial. 3. M. bovis prevalence was consistently higher at low badger de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
19
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 56 publications
9
19
1
Order By: Relevance
“…However, it is notable that dataset 1 conforms to a pattern whereby, within culling areas, the benefits of badger culling increase with increasing distance from the culling area boundary, while adverse impacts predominate on the periphery of culling areas; effects which are consistent with a range of findings suggesting that changes to the ways in which badgers interact are more pronounced close to culling area boundaries (Donnelly and others 2003, Woodroffe and others 2006, 2009, Donnelly and others 2007, Jenkins and others 2010a). …”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, it is notable that dataset 1 conforms to a pattern whereby, within culling areas, the benefits of badger culling increase with increasing distance from the culling area boundary, while adverse impacts predominate on the periphery of culling areas; effects which are consistent with a range of findings suggesting that changes to the ways in which badgers interact are more pronounced close to culling area boundaries (Donnelly and others 2003, Woodroffe and others 2006, 2009, Donnelly and others 2007, Jenkins and others 2010a). …”
Section: Discussionsupporting
confidence: 66%
“…Such increased transmission may be related to changes in bTB prevalence in badgers, which Woodroffe and others (2009) have shown can be consistently higher at low badger densities, within small social groups, and among badgers whose genetic profiles suggested that they have immigrated into social groups, although the absolute number of infected badgers has been found to be higher at higher population densities.…”
mentioning
confidence: 93%
“…Few datasets exist for natural systems that address the relationship between host density and pathogen transmission [but for timeseries analyses see: 46], [47], [48]. We showed that the seroprevalence of brucellosis in Wyoming elk is increasing in some regions where elk are not artificially aggregated onto supplemental feeding grounds and these increases in seroprevalence are correlated with elk densities at the hunt area scale (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Evaluation of the ecological impact of badger culling during the Randomised Badger Culling Trial identified an increase in fox abundance associated with reductions in badger density26 while reciprocal relationships between hedgehog Erinaceus europaeus and badger distributions suggest that increasing badger numbers might have had a negative impact on hedgehogs27. In terms of tuberculosis epidemiology, at a local level, disease prevalence and incidence appears to vary with mobility among groups28 and prevalence has been shown to be higher in smaller social groups29. Consequently, despite a broad landscape scale correlation between the incidence of TB in cattle and the distribution of badgers30, badger social group density alone may not predict patterns of TB infection in badgers or cattle.…”
Section: Discussionmentioning
confidence: 99%